MEASUREMENT SYSTEMS: CHARACTERISTICS AND MODELS - Abdu Idris Omer; M.M. Taleb (European Scientific Journal, ESJ, 2014)
In this paper, the major static characteristic parameters for sensors and instruments are defined and explained. Also, the process of calibration and subsequent characterization of errors are illustrated. Moreover, we describe the response and models of first and second order instrument to step and sinusoidal inputs.